Landmarks revisited : the Vekhi symposium 100 years on (2013)
The symposium entitled Vekhi, or Landmarks, is one of the most famous publications in Russian intellectual and political history. Its fame rests on the critique it offers of the phenomenon of the Russian intelligentsia. It was published in 1909, under the editorship of Mikhail Gershenzon, as a polemical response to the revolution of 1905, the failed outcome of which was deemed by all the Landmarks contributors to exemplify and illuminate fatal philosophical, political, and psychological flaws in the revolutionary intelligentsia that had sought it. Its fame persists until today not least because the volume has been deemed by many in Russia and the West to have proven prophetic in its prediction (and urgent warning) that the realization of the intelligentsia?s platform would bring ruin upon Russia. More than any other text, its republication in 1991 symbolically heralded the end of the ideological hegemony of Marxist-Leninism in the Soviet Union